Model for Developing Pancasila Student Profile Strengthening Project Based on Gender Relations - Listanto, Virgiawan; Sipahutar, Nova Yulanda Putri; Aflahah, St.; Muntakhib, Ahmad (LPPM Universitas Pendidikan Mandalika, 2024)
This study proposes a novel model for developing the Pancasila Student Profile Strengthening Project (P5) based on gender relations. The model aims to improve teachers' understanding and implementation of P5 by incorporating gender equality principles. Employing a qualitative approach with a Research and Development method, the study gathers data through interviews and Focus Group Discussions with key stakeholders, including students, P5 facilitators, principals, and school supervisors in junior high schools across Boyolali, Madiun, Tuban, Yogyakarta City, and Balikpapan. Thematic analysis of the qualitative data guides the model development process. Anchored in the regulatory guidelines established by the Ministry of Education, Culture, Research and Technology, the model offers innovative instructions for teachers and P5 facilitators to integrate gender considerations into various aspects of P5 implementation. This includes forming balanced project groups, selecting resources free from gender bias, and designing learning activities that promote inclusivity and equity. The proposed model offers innovation by integrating gender relations at every stage of developing the Pancasila Student Profile Strengthening Project, ensuring equal access, fair assessment, and materials that reflect gender diversity to strengthen inclusivity and equity in education.